Formulation and evaluation of enteric coated microcapsules of diclofenac sodium for modified release by combination of wet granulation and thermal change method - Bahadur, Sanjib; Baghel, Pragya; Chanda, Ranabir; Roy, Amit; Saha, Suman; Choudhury, Ananta (Journal of Applied Pharmaceutical Research, 2014)
The purpose of the present work was to develop optimized novel enteric microcapsules containing diclofenac sodium, a non steroidal anti inflammatory drug (NSAID) used for rheumatoid arthritis, for improved delivery and to diminish its adverse effect after oral administration. The microcapsule was prepared by using different polymers and the enteric coating was provided by using an innovative technique combining wet granulation method and thermal change method. This work also investigated different levels of enteric polymers like cellulose acetate phthalate (CAP) (X1) and ethyl cellulose (EC) (X2) and the stirring speed during coating ethyl cellulose (X3), by using 23 full factorial design. The dependent variables assessed were % yield (Y1), Q8 (% drug released after 8 hour) (Y2), n (Diffusion coefficient) (Y3), DEE (Drug entrapment efficiency) (Y4). The main effect and interaction terms were quantitatively evaluated using a mathematical model. The prepared microcapsules were evaluated for percentage drug dissolved, scanning electron microscopy, drug excipient interaction, angle of repose, particle size. Mean dissolution time (MDT) was used to compare dissolution patterns obtained. The results showed that X1 and X2 significantly affected the release properties.Â